PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA DIORAMA TERHADAP KETERAMPILAN MENULIS TEKS DISKUSI SISWA KELAS VIII MTs NEGERI MUARA BUNGO - Emidar, Sera Marini, Abdurrahman, (Universitas Negeri Padang, 2017)
The purpose of this study is (1) to determine the level of skill of writing disscusion text of grade VIII of MTs Negeri Muara Bungo before using problem based learning model with diorama media. (2) to determine the level of writing’s skill on disscusion text of grade VIII of MTs Negeri Muara Bungo after using problem based learning model with diorama media. (3) analyze the effect application problem based learning model with diorama media assisted to the skill of writing disscusion text in grade VIII students of MTs Negeri Muara Bungo. This type of research is quantitative experimental method. Based on data analysis, using problem based learning model with diorama media toward students writing’s skill on disscusion text in grade VIII students of MTs Negeri Muara Bungo. Kata kunci: pengaruh, model problem based learning, media diorama, keterampilan menulis teks diskusi